2020
DOI: 10.3389/fpsyt.2020.00513
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol Responses to Naturally Occurring Psychosocial Stressors Across the Psychosis Spectrum: A Systematic Review and Meta-Analysis

Abstract: healthy controls and psychosis spectrum groups were observed for only one of the six stressor-cortisol pairings examined, where life event exposure and diurnal cortisol were positively correlated in controls [r=0.25 (95% CI: 0.01 to 0.46)], but negatively correlated in the psychosis spectrum group [r=-0.28 (95% CI:-0.49 to-0.04)]. Conclusions: Overall, we observed poor concordance between naturally-occurring psychosocial stressors and cortisol irrespective of stressor type, cortisol measure, or group status. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 76 publications
(189 reference statements)
0
13
0
Order By: Relevance
“…Nonetheless, only scarce research has found an association between early adversity, life events or perceived stress and hair cortisol, and the direction of the associations has been contradictory among studies. Cullen and colleagues ( 62 ) reviewed studies examining the concordance between psychosocial stressors and cortisol measures in healthy controls, individuals at clinical high-risk for psychosis and with clinical psychosis, and only weak correlations were found. The present study complements the studies reviewed ( 62 ) by focusing on non-clinical individuals with psychometric high risk, although more research on the psychoendocrine covariance across the psychosis continuum is needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, only scarce research has found an association between early adversity, life events or perceived stress and hair cortisol, and the direction of the associations has been contradictory among studies. Cullen and colleagues ( 62 ) reviewed studies examining the concordance between psychosocial stressors and cortisol measures in healthy controls, individuals at clinical high-risk for psychosis and with clinical psychosis, and only weak correlations were found. The present study complements the studies reviewed ( 62 ) by focusing on non-clinical individuals with psychometric high risk, although more research on the psychoendocrine covariance across the psychosis continuum is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Shapero and colleagues ( 26 ) did not find any association between HCC and number of life events, whereas Xu's ( 27 ) and Karlén's ( 61 ) studies reported a positive association and Sierau's ( 31 ) a negative one. Finally, Cullen and colleagues ( 62 ) reviewed the literature examining the concordance between naturally-occurring psychosocial stressors, both distal (trauma) and proximal (perceived stress and life events), with cortisol across clinical and at-risk psychosis populations. Although all types of cortisol measurements were included in the meta-analysis, a poor correlation [ r = 0.05 (95% CI: −0.00 to 0.10), p = 0.059] was found between stressors and cortisol measures (including HCC).…”
Section: Introductionmentioning
confidence: 99%
“…In support of the model, patients with psychosis and those at increased risk for the disorder (due to a family history of illness or clinical features) have been found to show HPA axis abnormalities, including elevated basal and diurnal cortisol, a blunted cortisol awakening response and pituitary volume abnormalities (Berger et al, 2016; Borges, Gayer-Anderson, & Mondelli, 2013; Chaumette et al, 2016; Cullen et al, 2014; Day et al, 2014; Girshkin, Matheson, Shepherd, & Green, 2014; Nordholm et al, 2013; Saunders, Mondelli, & Cullen, 2019). However, a recent meta-analysis of 134 effect sizes from 18 studies (Cullen et al, 2020) found that, in psychosis spectrum groups and healthy controls, psychosocial stressors were only weakly (and not significantly) correlated with cortisol measures. Whilst these findings imply that the HPA abnormalities characterising psychosis spectrum groups are not driven by psychosocial stressors, the authors identified a range of methodological issues that may have obscured the ability to detect significant associations.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis demonstrated poor concordance between naturally-occurring stressors and the HPA axis dysfunction in patients with psychosis [19]. Apart from certain methodological considerations, it should be noted that exposure to ACEs is not a risk factor specifically associated with the psychosis spectrum.…”
Section: Introductionmentioning
confidence: 99%